Characterization of Ferroelectric Characteristics for Hafnium Zirconium Oxide Capacitors with Refractory Electrodes. (1st May 2022) - Liang, Yan-Kui; Lin, Jing-Wei; Huang, Yi-Shuo; Lin, Wei-Cheng; Young, Bo-Feng; Shih, Yu-Chuan; Lu, Chun-Chieh; Yeong, Sai Hooi; Lin, Yu-Ming; Liu, Po-Tsun; Chang, Edward Yi; Lin, Chun-Hsiung
Abstract : In this work, we investigated the ferroelectric properties of Hf0.5 Zr0.5 O2 (HZO) Metal-Ferroelectric-Metal (MFM) capacitors on various refractory electrodes, including TiN, TaN, W, and Mo. By comparing different electrodes and annealing temperature, we found that the MFM capacitors with TiN and W electrodes showed both higher remanent polarization (2Pr ) and lower leakage current for post-metal annealing (PMA) temperatures ranging from 400 °C to 600 °C. Moreover, the MFM capacitor with W electrode showed better saturated polarization-voltage (P-V) curve and less "wake up effect" during the polarization switching cycles, while the MFM capacitor with TiN electrode showed the lowest leakage current. The correlation of crystallization quality studied by X-ray diffraction and the ferroelectric characteristics for each type of MFM capacitors were also presented and compared in this study.